STRATEGI PENGHIMPUNAN DAN PENGEMBANGAN WAKAF UANG DI BADAN WAKAF UANG MUHAMMADIYAH SUMATERA BARAT - Afriyuda, Erik; Wira, Ahmad; Tiswarni, Tiswarni; Setiawan, Fadli (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research is motivated by the activities of the Muhammadiyah Cash Waqf Board (BWUM) of West Sumatra in both the collection and development of cash waqf funds. BWUM also serves as an active and professional nazhir (waqf manager) in managing these funds. The main research question is: what are the strategies employed by BWUM of West Sumatra in collecting and developing cash waqf, and what are the supporting and inhibiting factors in these processes? Based on the research findings, it is revealed that: a) the fundraising strategy used by BWUM West Sumatra follows a corporate fundraising approach. BWUM collaborates with wakif (waqf donors) to collect cash waqf funds through several partnerships, including with Muhammadiyah University of West Sumatra, BTM West Sumatra, and other parties such as stores, supermarkets, mosques, and offices. b) The strategy for developing cash waqf at BWUM West Sumatra involves two main approaches: first, direct investment in the real sector, such as organic catfish farming, sugarcane plantations, establishing a "Berkah" trading business, and investment in Pertashop; second, indirect investment through Islamic financial institutions, such as mudharabah deposits at BTM West Sumatra. Keyword: Fundraising Strategy, Development Strategy, Cash Waqf, BWUM West Sumatra. Abstrak: Penelitian ini dilatarbelakangi oleh kegiatan Badan Wakaf Uang Muhammadiyah Sumatera Barat dalam penghimpunan maupun dalam mengembangkan dana wakaf uang. Dan juga merupan nazhir wakaf uang yang aktif dan profesional dalam pengelolaannya. Dalam hal ini, yang menjadi pertanyaan penelitian adalah: bagaimana strategi Badan Wakaf Uang Muhammadiyah Sumatera Barat baik dalam penghimpunan maupun dalam pengembangan wakaf uang, serta faktor-faktor yang menjadi pendukung dan penghambat dalam menghimpun dan mengembangkan dana wakaf uang. Dari hasil penelitian yang dilakukan diketahui bahwa: a. strategi penghimpunan yang dilakukan oleh BWUM Sumatera Barat adalah strategi corporate fundraising. BWUM Sumatera Barat menjalin kerjasama dengan wakif untuk menggalang dana wakaf uang. Strategi yang dilakukan adalah: pertama, kerjasama dengan UM Sumatera Barat. Kedua, Kerjasama dengan BTM Sumatera Barat. Ketiga, kerjasama dengan pihak lain seperti toko, swalayan, masjid, dan perkantoran. b. Strategi pengembangan wakaf uang di BWUM Sumatera barat adalah dengan: pertama, berinvestasi langsung pada pada sektor ril seperti peternakan lele organik, perkebunan tebu, mendirikan usaha dagang berkah, dan investasi pada perthashop. Kedua, beinvestasi tidak langsung pada lembaga keuangan syariah seperti deposito mudharabah pada BTM Sumatera Barat. Kata kunci: Strategi Penghimpunan, Strategi Pengembangan, Wakaf Uang, BWUM                    Sumatera Barat.